Renal Insufficiency and Mortality in Patients with Known or Suspected Coronary Artery Disease - van Domburg, Ron T. (American Society of Nephrology, 2008)
It remains unclear whether mild renal dysfunction is associated with adverse cardiovascular outcome. We investigated whether estimated glomerular filtration rate (eGFR) was associated with mortality and cardiac death among 6447 patients with known or suspected coronary artery disease over a mean follow-up of 7 yr. Cumulative 5- and 10-yr survival rates decreased in a graded fashion from 88% and 70%, respectively, for those with normal renal function to 43% and 33% for those with eGFR <30 ml/min. Compared with patients with normal renal function, the multivariable adjusted hazard ratios for all-cause mortality among patients with mild, moderate, and severe renal impairment were 1.33 (95% confidence interval [CI], 1.21–1.48), 1.67 (95% CI, 1.44–1.93), and 3.38 (95% CI, 2.73–4.19), respectively. Similar relationships between cardiac death and decreasing renal function were found. In conclusion, renal function is a graded and independent predictor of long-term mortality in patients with known or suspected coronary artery disease. Intense treatment and close surveillance of these patients is encouraged.